Surtitling for Mandarin theatre : a user-centred approach to translating Singlish - Lin, Hui (Nanyang Technological University, 2020)
Surtitling is a relatively new field in translation studies with little to no previous research done in Singapore. The increasing use of surtitles worldwide, coupled with declining standards of mother tongue language in Singapore, meant that its use in the local theatre scene, especially in non-English theatre performances, is gaining popularity and importance. Singlish, being quintessentially Singaporean, is being used with increasing fervour in plays that are set locally. However, it poses a challenge to surtitle translators in deciding to what strategies to employ to best conduct this transfer of language and culture. There is a constant tug-o-war between preserving the Singlish flavour in the surtitles and risking alienating members of audience who might not be attuned to the specific culture, or neutralizing the Singlishness in the surtitles and providing a culturally neutral version of the show. This paper seeks to take a user-centred approach to understanding the preferences of the audience through conducting a survey, in hope that it can serve as a guide for Singlish surtitle translation. Data collected from an online survey did not point to any clear consensus on whether Singlish or standard English is preferred in translating local Mandarin plays that contain Singlish. However, surtitles in standard English scored better in overall usability, especially in the areas of readability and comprehensibility, and hence is the recommended approach.